Proyeksi Pertumbuhan Penduduk terhadap Peningkatan Jumlah Sampah di Tempat Pembuangan Akhir (TPA) Regional Kota Payakumbuh - Milenia, Indri; Iskarni, Paus (Al-DYAS, 2025)
This study aims to (1) determine the rate of population growth on the increase in the amount of waste in the Payakumbuh City Regional Final Disposal Site (TPA), (2) determine the capacity of the Payakumbuh City Regional TPA in 2028. This type of research is quantitative descriptive. The data analysis technique used is using the population growth rate formula, prediction of the amount of waste and data processing methods using manual calculations, namely with the geometric equation formula to predict the amount of waste entering the Payakumbuh Regional TPA. The results of this study indicate that the Payakumbuh Regional TPA is used by 4 cities/regencies, namely, Payakumbuh City with a population of 316,371 people in 2028, Bukittinggi City with a population of 146,978 people in 2028, 50 Kota Regency 699,349 people and Agam Regency 999,072 people. The increase in the amount of waste each year is influenced by changes in the population and waste production per resident per year. The waste production entering the Payakumbuh Regional Landfill until 2028 is 3,431.17 tons. The capacity will experience an overload in 2028 with an overload of 2,287.44 m3 with a height of 1.65859 meters from the planned height of 1.65859 meters.